Metformin alone and in combination with sitagliptin induces depression and impairs quality of life in type 2 diabetes mellitus patients: An observational study - Athar, Mohammed; Garg, Aakriti; Khan, Mohd Ashif; Parveen, Rizwana; Kohli, Sunil; Vohora, Divya; Nidhi (International journal of clinical pharmacology and therapeutics, 2023)
Various studies have reported the association of cognition and depression with diabetes. Literature suggests that metformin and sitagliptin used to control hyperglycemia in type 2 diabetes mellitus (T2DM) possess a beneficial effect on neurological symptoms associated with diabetes. However, there are scarce data in the clinical setting. Thus, this study aims to compare depression, cognitive impairment, and quality of life (QoL) of newly diagnosed T2DM patients with those of healthy individuals. Further, the impact of metformin alone or in combination with dipeptidyl peptidase-4 inhibitors on cognition, depression, and QoL of T2DM patients was also compared with newly diagnosed T2DM patients. This was a prospective observational study in 120 subjects. The subjects were equally divided into four groups: healthy controls, newly diagnosed T2DM patients, and T2DM patients taking either metformin alone or in combination with sitagliptin. We assessed cognition using Mini-Mental State Examinations (MMSE), depression using Hamilton Depression Rating Scale (HAM-D), and health status using Short-Form Health Survey-36 (SF-36). No significant change in MMSE score was observed among the groups. However, a significant increase in the HAM-D score of newly diagnosed patients (p < 0.001), T2DM patients receiving metformin alone (p < 0.05), and in combination with sitagliptin (p < 0.001) was observed as compared to healthy controls (p < 0.001). Also, a statistically significant increase in HAM-D score was observed in patients receiving sitagliptin in combination with metformin as compared to metformin alone (p < 0.01). A decrease in SF-36 scores was observed in all groups as compared to healthy controls. To conclude, this preliminary study indicates that T2DM patients are most likely to suffer from depression and impaired QoL. Moreover, both the conventional and recent antidiabetic agents might lead to neurobehavioral complications and adverse impact on the QoL of these patients. Thus, we warrant the assessment of cognitive functions, depression, and QoL in patients receiving metformin and sitagliptin.